2019
DOI: 10.2147/ott.s216086
|View full text |Cite
|
Sign up to set email alerts
|

<p>Construction of a nomogram for the prediction of prognosis in patients with resectable gastric cancer undergoing fewer than sixteen lymph node biopsies</p>

Abstract: BackgroundLymph node metastases evaluation is important for assessing gastric cancer prognosis. In patients not undergoing adequate lymph node biopsy, lymph node stage migration occurs with the use of the existing staging system. This study established a prediction model to improve prognostication in patients undergoing fewer than 16 lymph nodes biopsy.Patients and methodsIn total, 3036 eligible patients from the Surveillance, Epidemiology, and End Results Program database were evaluated. They were randomized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…A nomogram was developed from the results of the Cox regression analysis, and it was used to predict the 3-and 5-year overall survival by representing the sum of points for each variable. 17 The internal validation of the model was performed using a 1000 bootstrap resample. The C-index, which denotes the proportion of pairs, measured on a scale of 0.5 (no better than chance) to 1 (perfect discrimination), was calculated to verify the nomogram's predictive accuracy, with the responder having a higher predicted probability of response than the non-responder.…”
Section: Discussionmentioning
confidence: 99%
“…A nomogram was developed from the results of the Cox regression analysis, and it was used to predict the 3-and 5-year overall survival by representing the sum of points for each variable. 17 The internal validation of the model was performed using a 1000 bootstrap resample. The C-index, which denotes the proportion of pairs, measured on a scale of 0.5 (no better than chance) to 1 (perfect discrimination), was calculated to verify the nomogram's predictive accuracy, with the responder having a higher predicted probability of response than the non-responder.…”
Section: Discussionmentioning
confidence: 99%
“…The Stomach Adenocarcinoma (STAD) dataset from TCGA was processed by deleting blank values for further analysis, and the thresholds used to divide patients by age, tumor grade, TNM stage, T stage, N stage, M stage, and percentage of positive lymph nodes were in accordance with other previous studies [23][24][25][26][27][28][29]. Based on the results of the χ 2 test and LASSO regression, some important variables were selected, and Cox regression analysis was used to construct a nomogram using the rms package in R software.…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies have suggested that a C-index ranging from 0.50-0.70 indicates a low degree of distinction, a moderate degree of distinction between the interval 0.70 and 0.90, and a high degree of distinction higher than 0.90. 22 Stratification analyses visualized by tree diagrams were used to evaluate the performance of the LODDS classification in distinguishing heterogeneous patients within various groups according to the results of the multivariate analyses.…”
Section: Discussionmentioning
confidence: 99%